The United Kingdom Primary Immune Deficiency (UKPID) registry 2012 to 2017. (25th May 2018) - Shillitoe, B; Bangs, C; Guzman, D; Gennery, A R; Longhurst, H J; Slatter, M; Edgar, D M; Thomas, M; Worth, A; Huissoon, A; Arkwright, P D; Jolles, S; et al.
Summary: This is the second report of the United Kingdom Primary Immunodeficiency (UKPID) registry. The registry will be a decade old in 2018 and, as of August 2017, had recruited 4758 patients encompassing 97% of immunology centres within the United Kingdom. This represents a doubling of recruitment into the registry since we reported on 2229 patients included in our first report of 2013. Minimum PID prevalence in the United Kingdom is currently 5·90/100 000 and an average incidence of PID between 1980 and 2000 of 7·6 cases per 100 000 UK live births. Data are presented on the frequency of diseases recorded, disease prevalence, diagnostic delay and treatment modality, including haematopoietic stem cell transplantation (HSCT) and gene therapy. The registry provides valuable information to clinicians, researchers, service commissioners and industry alike on PID within the United Kingdom, which may not otherwise be available without the existence of a well-established registry. Graphical Abstract: